2021
DOI: 10.1172/jci.insight.146945
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of high-mannose, fucosylated, and complex N-glycans in breast cancer metastasis

Abstract: BACKGROUND. Although aberrant glycosylation is recognized as a hallmark of cancer, glycosylation in clinical breast cancer (BC) metastasis has not yet been studied. While preclinical studies show that the glycocalyx coating of cancer cells is involved in adhesion, migration, and metastasis, glycosylation changes from primary tumor (PT) to various metastatic sites remain unknown in patients. METHODS. We investigated N-glycosylation profiles in 17 metastatic BC patients from our rapid autopsy program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…N -linked and O -linked glycosylation use UDP-GlcNAc as substrate to modify the activity of metabolic enzymes, transcription factors, and several signalling molecules ( 63 ). Furthermore, N -glycosylation has been proven to be elevated in elevated in breast cancer primary tumors, as well as in lymph node metastases and distant metastases compared to healthy mammary tissue ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…N -linked and O -linked glycosylation use UDP-GlcNAc as substrate to modify the activity of metabolic enzymes, transcription factors, and several signalling molecules ( 63 ). Furthermore, N -glycosylation has been proven to be elevated in elevated in breast cancer primary tumors, as well as in lymph node metastases and distant metastases compared to healthy mammary tissue ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in baseline glycosylation in normal breast tissue may be contributing to specific differences in breast stromal biology disproportionally affecting BW. While previous studies have shown that increased fucosylation is associated with malignancy ( 38 , 41 , 88 90 ), one study found that a specific fucosylated glycan structure had been shown to be relatively higher in normal breast compared to breast tumors, both from breast cancer patients ( 91 ). Based on the previous findings and our current study, it may not be appropriate to generalize fucosylation patterns in breast tissue as distinct fucosylated structures may have distinct associations in normal versus malignant tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Fucosylation is a well-known glycosylation modification that has been well characterized in cancers ( 32 , 35 , 38 , 48 , 49 , 92 , 93 ). Variations in fucosylation linkages such as outer-arm fucosylation and core-fucosylation have distinct implications for cancer biology ( 27 , 28 , 32 , 35 , 38 , 42 , 92 ). In fact, increased fucosylation, both core and branched segments, have been observed in malignant transformation in many cancers such as breast ( 38 , 41 ), liver ( 66 ), pancreatic ( 94 ), prostate ( 61 ) and colorectal cancers ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation of the dysregulation of N -glycan patterns in PTMC may point to pathophysiological processes involving multiple proteins, as we discuss below. Early studies showed that the high-mannose glycans and complex-type glycans were increased in breast cancer progression, and glycans took part in cancer progression phases, such as cell proliferation signaling, activating invasion and metastasis, and tumor-promoting inflammation [ 36 , 37 , 38 ]. Chik et al have shown high-mannose structures as the most abundant glycan in colorectal cancer cell lines and tissues [ 39 ].…”
Section: Discussionmentioning
confidence: 99%